Insight into Anticorrosion Mechanism of Ampicillin on Mild Steel in Acidic Environment: A Combined Experimental and Theoretical Approach - Tuan Dinh; Nguyen Minh Thong; Dinh Quy Huong; Trinh Le Huyen; Tran Duc Manh; Phan Tu Quy; Tran Xuan Mau; Pham Cam Nam (Journal of Chemistry)
The corrosion inhibition of mild carbon steels in an acidic environment by using ampicillin (AMP) has been evaluated based on experimental and quantum chemistry techniques. The experimental results indicate that the inhibition efficiency goes up at higher AMP concentration. The highest inhibition efficiency reaches 84.9% for polarization measurement and 90.1% for electrochemical impedance spectroscopy with the inhibitor of concentration 100 ppm at 298 K. The surface characteristics (SEM) also reconfirm the steel corrosion inhibition ability of AMP. Some important chemical factors such as EHOMO (highest occupied molecular orbital energy), ELUMO (lowest unoccupied molecular orbital energy), ΔEL−H (energy gap), and Fukui functions were calculated based on the optimized configuration of AMP at the theoretical level of B3LYP/6-31+G(d,p). Moreover, Monte Carlo and molecular dynamics simulations were used to analyze the absorption behavior of inhibitor on the surface of Fe(110), which supplies the mechanism of inhibition corrosion processes. The obtained results showed that AMP is considered to be a potential corrosion inhibitor for mild steel in 1M HCl medium. Moreover, the protonated state of AMP plays an important role in the protection of Fe surface against the corrosive process.